Peningkatan Kesadaran dan Kewaspadaan Anak Sekolah dan Masyarakat dalam Pencegahan dan Penanggulangan COVID-19 - Iha Zakiyah (Jurnal Pengabdian Masyarakat PGSD, 2021)
Community Service program is a mandatory program must be attended by students at several university including Universitas Pendidikan Indonesia. This activity should go to the villages directly, but because of Covid-19 the activities become online. This program used descriptive qualitative. This program started from November 16th until December 30th, 2020 with a demand time that must be taken is 120 hours. The program which was held by UPI during the Covid-19 pandemic carried the theme Thematic Community Service Lecture on the Prevention and Overcoming of the Impact of Covid-19. The program was held in Serang, Banten by online to prevent the spread of Covid-19. There are mandatory program and two optional programs in education and economic sectors. This program conducted a combination of strengthening student online learning, mentoring and parents during online schooling, helping school administration, making educational videos on programs to mitigate the impact of COVID-19 in the field of education which are shared on Instagram and Youtube, and making news articles published to mass media..